Syntactic and semantic variations in negative interrogatives: Contracted vs. uncontracted forms - Khalsiah Khalsiah; Burhanuddin Yasin; Muhammad Yusuf; Fatmawati Fatmawati (Universitas Syiah Kuala, 2024)
This study investigates the forms and uses of negative interrogatives with auxiliary verb contractions in English, focusing on syntactic and semantic differences. Data was drawn from conversations in an English class at a university in Lhokseumawe, Indonesia, between a lecturer and students and students and students. The aim was to examine three types of negative interrogatives: Yes-No questions, negative rhetorical questions, and both marked (nt) and unmarked (not) forms. The research employs a descriptive method with a synchronic time frame, utilizing distributional analysis, including immediate constituent analysis and mark reading techniques, to categorize and analyze the data. The findings reveal that negative interrogatives involving auxiliary verbs exhibit positive and negative presuppositions, with adjectival negative interrogatives showing variations between contracted and uncontracted forms. Adverbial negative interrogatives were found across all three types, indicating their versatility in forming questions. The study highlights that the choice between not and nt affects the tone and emphasis of negative interrogatives, influencing the interpretation of responses. Contracted forms often carry a rhetorical or presumptive tone, while uncontracted forms are more formal and explicit. These variations show the importance of auxiliary verbs and negative markers in shaping the structure and meaning of negative interrogatives. This research contributes to the understanding of how negative interrogatives function in English, revealing the nuanced ways in which they impact communication and interpretation.